Bol' v nizhney chasti spiny u molodykh - novyy podkhod k terapii - Nadezhda Aleksandrovna Shostak; Natal'ya Grigor'evna Pravdyuk; Inna Nikolaevna Koryakina; N A Shostak; N G Pravdyuk; I N Koryakina (Терапевтический архив, 2009)
Aim. To evaluate the efficiency and safety of arthrofoon versus sublingual nimesulide in patients with degenerative disc disease (DDD) in two parallel groups. Subjects and methods. Fifty patients (males and females) aged 18-35 years who had acute and chronic low back pain (LBP) (visual analog scale (VAS), > 40 mm) associated with DDD were enrolled in the study. Therapeutic efficiency was evaluated from the intensity of pain (VAS), spinal function (Schober's test and Tomayer's test), the severity of disease (VAS), assessed by a physician and a patient, and the frequency of recurrent pain episodes. Results. The evaluation of the efficacy of arthrofoon showed a statistically significant positive change in pain (VAS), which corresponded to that in the indices of the pain syndrome during nimesulide administration. There was a statistically significant reduction in the frequency of recurrences in patients with chronic intermittent LBP treated with arthrofoon (p < 0.01). Arthrofoon used alone and in combination with paracetamol demonstrated a good safety profile. Conclusion. In DDD-associated LBP, the use of arthrofoon is effective and safe in young patients with both the acute (in combination with nonsteroidal anti-inflammatory drugs as a short course) and chronic (requiring long-term anti-inflammatory therapy) types of the disease.